The Sociocultural and Institutional factors influencing Tax Avoidance in sub-Sahara Africa - Alfred James Kimea; Msizi Mkhize; Haruna Maama (Cogent Business & Management, 2023)
Businesses find ways to reduce their tax while the government also establishes laws and policies to prevent tax avoidance. These conflicting objectives and strategies have heightened the interest in establishing the factors that influence firms' level of tax avoidance. The study examined a country's institutional and sociocultural elements that influence tax avoidance practices by firms in sub-Saharan Africa (SSA). The study involved one hundred seventy-three (173) listed companies from eight sub-Saharan African countries. The study used a multiple regression analysis technique to estimate the results. The results showed that a country's institutional settings and particular sociocultural practices impact its firms' tax avoidance practices. The findings demonstrated that the degree of tax avoidance activities of firms in SSA is influenced by management quality, regulatory quality, auditing quality, culture, and ethics of a country. This result has several policy implications. First, the management of firms can use their resources to lower the tax paid to the government. Governments can also use institutional frameworks to stop businesses from using aggressive tax avoidance strategies. As a result, the study adds to the body of research on the factors influencing tax evasion in emerging markets. The findings align with the institutional theory's assertions that institutions, laws, and regulations can impact how businesses behave through coercive and normative isomorphism, which can affect how they avoid paying taxes.
Keywords: 650; culture; audit quality; ethics; Tax avoidance; tax planning; management quality